IMPLEMENTASI AKAD ISTISHNA PADA HOME INDUSTRY MAMA AWAH JAHIT DI KELURAHAN SUMURPECUNG KOTA SERANG - Nazwa Septiani; Fidela Syahda; Fany Cahyaningsih; Dea Anastya Putri; Mukhlishotul Jannah (Cahaya Ilmu Bangsa, 2024)
This research aims to analyze the application of the istishna contract in buying and selling transactions at the